Holographic Origin of High Cosmological Constant Related to Large Mass Defect in Semiclosed Friedman Universe (Global Journal of Science Frontier Research, 2014)
An extremely high value of Einstein's cosmological constant Λ ~10 122 in quantum cosmology compared to astronomical observations, 0 ≤ Λ ≤ 1, is related to the extremely large general relativistic mass defect of massive semiclosed universe.
Keywords: cosmology; general relativity; quantum theory; information theoy; holography